If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(h + -4) + 5 = 60 Reorder the terms: 3(-4 + h) + 5 = 60 (-4 * 3 + h * 3) + 5 = 60 (-12 + 3h) + 5 = 60 Reorder the terms: -12 + 5 + 3h = 60 Combine like terms: -12 + 5 = -7 -7 + 3h = 60 Solving -7 + 3h = 60 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 3h = 60 + 7 Combine like terms: -7 + 7 = 0 0 + 3h = 60 + 7 3h = 60 + 7 Combine like terms: 60 + 7 = 67 3h = 67 Divide each side by '3'. h = 22.33333333 Simplifying h = 22.33333333
| 13x+2x=-150 | | 5m+42=11m | | (4x)*2=16 | | 5(8x-4)=44x | | 2-(x+5)=4x-8 | | 3(x+8)=33 | | 6(6n+7)=7(6n+6)+5 | | 7x-x=36 | | 5w+10=0 | | 6x-5y=9 | | 16(x+2)=4(4x+1)+28 | | -20y=120 | | 6x=32-2x | | 40=18x-10x | | -3(x+5)+5x=10 | | 10x^2+7x-5=0 | | 6+x=32-x | | 9x-x=40 | | 5x+2(x+8)-6(4x-5)= | | -3x^2+7x=-10 | | 8xy+6yz-4xz-8xy= | | -47-18=13a | | -1(z-6)=-20 | | -7+8x=19x+15 | | -p=2 | | -6x+9=3x-27 | | (y+3)(y+5)= | | (3b^3+9b^2-3)+(2b^3-9b+7)= | | (15-7)x=(11+5)x | | -9=9(y+3) | | 3x+4(2-x)=4x+5 | | 4(2x)=72 |